Synthesis and Biological Evaluation of Some New 1,2,3-Triazole Derivatives As Anti-microbial Agents (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
A series of 1,2,3-triazole derivatives bearing different chemical entities were prepared starting from 2-(4-phenyl-1H-1,2,3-triazol-1-yl)acetohydrazide, compound 2. The purity of all new compounds was checked by TLC and elucidation of their structures was confirmed by IR, 1H and 13C NMR along with High Resolution Mass Spectrometry (HRMS). All the target compounds were evaluated for their possible antimicrobial activity. Most of the tested compounds showed moderate to good antibacterial activity against most of the bacterial strains used in comparison with ciprofloxacin as a reference drug. The most active compounds were 4a, 9a, 9b, and 9f. Results of antifungal activity revealed that most of the tested compounds showed a good antifungal activity in comparison to fluconazole as a reference drug. Compounds 4a, 9c, 9d and 9f were the most active ones.